The image of marginalized in two plays of J. L. Alonso de Santos (Ogigia. Revista Electrónica de Estudios Hispánicos, 2016)
This paper aims at analyzing the concept of social marginalization and its relationship to capitalism based on two plays: José Luis Alonso de Santos: La estanquera de Vallecas(1985) and Bajarse al moro (1981), within the social context of Spain during 1980s–1990s. This analysis will shed light on the relation among those who are marginalized or integrated in the community. In fact, there are many differences between the two plays; however they both share the main theme in terms of the effort exerted by the marginalized to be integrated in a community that does not recognize him/her. Another dimension addresses the relationship of this effort to the functioning of capitalism and its by product, the consumptive community.
Keywords: marginalization; La estanquera de Vallecas; Bajarse al moro; drama criticism